Development of a Class IIB Pati Prison Inmate Processing System Using Barcodes - Prabowo, Renaldy Tirto; Nindyasari, Ratih; Wijayanti, Esti (Journal La Multiapp, 2025)
Correctional facilities in Indonesia face significant challenges in inmate management due to reliance on manual, paper-based systems for room occupancy verification, leading to inefficiencies, prolonged verification times, high potential for data errors, and substantial workload for correctional officers during frequent room reshuffling activities. This study aims to develop a web-based information system leveraging barcode technology to streamline the inmate verification process at Lapas Kelas IIB Pati, minimizing human error, enhancing administrative efficiency, and accelerating data management processes. The research employed a Research and Development (R&D) approach with qualitative methodology using the Waterfall model for system development, incorporating data collection techniques including observation, semi-structured interviews with correctional officers, literature review, and document analysis. The study population comprised all data management processes for inmates and officers at Lapas Kelas IIB Pati, with purposive sampling selecting key informants, relevant documents, and existing manual systems. System validation was conducted through Blackbox Testing to verify functional specifications and User Acceptance Testing (UAT) using Likert scale questionnaires to evaluate user satisfaction. The developed system successfully automated inmate verification through QR/barcode scanning, implemented role-based access controls, and provided room transfer functionality, with all system functionalities achieving successful outcomes in testing, demonstrating operational viability and significant improvement in efficiency and data accuracy. The web-based inmate processing system effectively addresses operational challenges in correctional facility management, providing a practical solution for digital transformation in Indonesian correctional institutions.